The State of Mis/Disinformation, Polarisation and State Threat to Ghana - Kwode, Paul Achonga Kabah; Atanga, Raphael Ane; Acharibasam, John Bosco; Tindi, Stephen (Media Foundation for West Africa, 2025)
Information disorder and other public discourse misconducts pervert the will of citizens and undermine public trust in democratic processes and institutions. In Ghana, the surge in information disorder presents a formidable threat to democratic sustenance, including elections. This exploratory study sought to ascertain the state of mis/disinformation, hate speech, polarising narratives, and state threat to Ghana. This study further analysed the nature of the threat, and identified the key actors, platforms, and mechanisms for driving these threats. It also analysed the role of social media in the dissemination of these narratives. Again, the study assessed the impact of these narratives on public perception, information integrity, election integrity and democratic consolidation in Ghana. The study provided recommendations for mitigating these threats, and promoting fact-based public discourse. A qualitative research approach was adopted with focus group discussions and in-depth interviews as primary sources of data collection. Purposive and snowball sampling strategies were employed to select the research participants. These included representatives from political parties, civil society organisations (CSOs), and state institutions; and journalists, youthful voters, and academics selected from Tamale, Kumasi and Accra. The geographical selection of the study sites ensured a fair representation from the north, middle and coastal belts of Ghana. Geographically, the study focused on the selected regions due to the following reasons: The three regions are apparently considered as the epicentres of political contest and polarising narratives. Ashanti region has been the stronghold of the NPP. Greater Accra is the host of the national capital, where a lot of the national debate and discourses on governance take place on the big media outlets, which have significant influence across the country. The Northern region is ostensibly home to many of the inter-ethnic and inter-communal conflicts in Ghana, and thus quite fragile in terms of potential for violence and polarisation. A thematic analysis of the qualitative data revealed that mis/disinformation, hate speech, and polarising narratives are alarmingly prevalent in Ghana at all levels of public discourse – community, regional and national. The phenomenon has become a constitutive part of political communication strategies of political parties, media, online content creators and malign foreign actors. The study reported some egregious incidence of hate speech. While political actors were the main spreaders and targets of mis/disinformation, hate speech and polarising narratives; mainstream media practitioners, sensational social media content creators, and malign foreign actors are also culpable. These bad actors use social media and politically aligned mainstream media to mislead citizens, obfuscate public debate, and degrade public confidence in democratic processes and institutions. The study recommended a holistic strategy to addressing the “wicked problem” of information disorder, hate speech, polarisation and state threat. Because the current measures such as fact-checking, pre-debunking and Media Information Literacy (MIL) are inadequate, the study recommended that platform owners and mainstream media owners are held accountable for public discourse misconducts on their platforms. Again, state actors and key collaborators should heighten MIL at all levels in order to counter information disorder and state threat. Also, media practitioners and media organisations—who are at the forefront of the information ecosystem—should continue to prioritise fact-based reporting and fact-checking to promote information hygiene, and preserve the integrity of Ghana's media system. Additionally, the study recommended regulation of social media by striking a balance between curbing mis/disinformation and freedom of expression online. Finally, the study reiterates the need to scale-up the existing interventions by the Media Foundation for West Africa (MFWA) and other collaborators which seek to promote fact-based discourse and information hygiene in Ghana.
Keywords: Misinformation; Disinformation; Polaisation; State threat; Ghana; MFWA